LA LUCHA INSURRECCIONAL (1952-1958) EN LAS TUNAS. SU REFLEJO EN LOS DOCUMENTOS HISTÓRICOS: THE INSURRECTIONAL STRUGGLE (1952-1958) IN LAS TUNAS PROVINCE. ITS REFLECTS ON THE HISTORICAL DOCUMENTS - Garcés Fernández, Eduardo; Ochoa Brito, María Antonia (Opuntia Brava, 2018)
El objetivo principal del trabajo es dar a conocer los hechos históricos de la época y cómo lo reflejaron los documentos históricos. No ha sido la intención escribir la historia completa del período. Se emplearon los métodos de estudio de los documentos históricos (fuentes escritas) y los testimonios (fuentes orales) para corroborar y verificar las informaciones. Se analizaron, cartas, partes y órdenes militares, telegramas e informes. Todo ello permitió elaborar una síntesis que recoge algunos hechos de la historia de Las Tunas de 1952-1958 enriquecida con documentos de la época. ABSTRACT The main objective of that work consists on let knowing the historical facts of the epoch and how historical documents. Show them on. The author’s intention is not making the complete history of that period. Some study methods were used from the historical documents (written fountains), and from testimony (oral fountains) to corroborate and verify the information. It was necessary to study letters, orders and military reports, telegrams and information. It let the author elaborate a synthesis which compiles some facts from the history (from 1952 to 1958) in Las Tunas city. It also was strengthen by some important documents from the epoch. KEY WORDS: historical facts, historical documents, insurrectional struggle, armed weapon’s groups, guerrilla, rebels